SALES MANAGEMENT INFORMATION SYSTEM WITH SITE PLAN VISUALIZATION AT PT.ALESTA PROPERTY INDONESIA - Nicky Fristyar, Bagas; Laily Fithri, Diana; Muzid, Syafiul (JATI (Jurnal Mahasiswa Teknik Informatika), 2025)
Housing consists of residential units equipped with adequate facilities, offering comfort and security. PT Alesta Property, a subsidiary of Alesta Group Indonesia, operates in housing development and sales but faces challenges in managing housing availability. Currently, information on availability, booking status, mortgages, and sales is only accessible via direct communication with administrators, leading to inefficiencies and errors. To address this, this research develops a web-based system using site plan visualization to display housing status clearly, minimizing miscommunication and enhancing transparency. A Customer Relationship Management (CRM) system is integrated to automate notifications, such as payment reminders and booking confirmations via WhatsApp, ensuring timely customer communication. The system improves efficiency in sales management, streamlines administrative processes, and enhances customer experience. Developed using the Waterfall method, it provides a structured approach to implementation. This research enables PT Alesta Property to optimize housing sales management and offer a more reliable and user-friendly experience for prospective buyers.